PHOTOFUNDUS CHARACTERISTIC OF DIABETES MELITUS PATIENT IN PRIMARY AND SECONDARY HEALTH CARE CENTERS - Winly, Winly; Ari Suryathi, Ni Made; Suryanadi, Ni Made; Andayani, Ari; Manuaba, Ida Bagus Putra (International Journal of Retina, 2024)
Introduction: The prevalence of diabetes mellitus increases over time in line with the prevalence of diabetic retinopathy is also expected to increase. It is not possible to determine which diabetic patients will have retinopathy, so therefore screening is needed. This study aims to have a better understanding in managing DM patients in the future, especially in cases of diabetic retinopathy in primary, secondary & community health care centers. Methods: A descriptive analytical study. Data collected cross sectional study based of characteristic and portable photo fundus from DM patients while doing social service at a health service center. Results: Portable photo fundus in this study, screening 138 DM patients, with majority of subjects is in the range 44-64 year age group (68.1%). There was the same number of patient between gender or type. History of DM in the family (63.0%) with a duration of DM ≤ 5 years (56.5%), mostly the quality of photo fundus that can be assessed (97.1%), patients who needed further treatment were referred to the ophthalmologist 59 cases (42.8%). Conclusion: People who live far from cities and have limited access to health facilities can be reached using this portable photo fundus, so that blindness in peripheral areas will be more easily detected and this can be used as a screening modality and blindness due to diabetic retinopathy can be prevented.